The mechanisms of recognition between legume roots and rhizobia: Some implications for biological nitrogen fixation in the tropics - Dazzo, F.B. (International Center for Tropical Agriculture, 1982)
This paper reviews the experimental basis for the lectin-recognition hypothesis and considers ways in which the host/Rhizobium interaction might be manipulated to enhance the benefits of symbiotic nitrogen fixation in the tropics.